2020
DOI: 10.15240/tul/001/2020-1-007
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of turnover intention: A meta-analysis study in the United States

Abstract: The purpose of this paper was to determine the direction and effect size of the relationships between turnover intention and its main antecedents in the United States. The main predictors of turnover intention are chosen as job satisfaction, organizational commitment and empowerment. The studies which are published between 1998 and 2018 are reviewed. ScienceDirect, Scopus, and ProQuest databases were searched and 2.356 studies are screened. The meta-analysis software package, Comprehensive Meta-analysis Softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 67 publications
4
28
0
1
Order By: Relevance
“…In contrast, factors that prevented nurses’ turnover intention were work engagement, job satisfaction and professional self‐concept. The finding that individual‐level predictors affect nurses’ turnover intention was consistent with findings in studies conducted in other countries (Chiang & Chang, 2012 ; Deery et al., 2011 ; Fasbender et al., 2019 ; Özkan et al., 2020 ; Simone et al., 2018 ; Zhao et al., 2018 ). In particular, job stress was shown to be prevalent in nursing positions and highly related to emotional exhaustion, depression, fatigue and burnout (Chiang & Chang, 2012 ; Trybou et al., 2014 ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In contrast, factors that prevented nurses’ turnover intention were work engagement, job satisfaction and professional self‐concept. The finding that individual‐level predictors affect nurses’ turnover intention was consistent with findings in studies conducted in other countries (Chiang & Chang, 2012 ; Deery et al., 2011 ; Fasbender et al., 2019 ; Özkan et al., 2020 ; Simone et al., 2018 ; Zhao et al., 2018 ). In particular, job stress was shown to be prevalent in nursing positions and highly related to emotional exhaustion, depression, fatigue and burnout (Chiang & Chang, 2012 ; Trybou et al., 2014 ).…”
Section: Discussionsupporting
confidence: 88%
“…In the present review, 170 related factors were identified in 417 studies that investigated the predictors of the turnover intention in hospital nurses. In the past 10 years, the number of relevant stud- Han & Jekel, 2011; Hayes et al, 2006;Oyeleye et al, 2013;Özkan et al, 2020;Simone et al, 2018;Yin & Yang, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations